2022
DOI: 10.1136/spcare-2022-003990
|View full text |Cite
|
Sign up to set email alerts
|

Cancer palliative care referral: patients’ and family caregivers’ perspectives – a systematic review

Abstract: BackgroundDespite the evidence of palliative care benefits, referrals are infrequent and delayed. Patients and their caregivers are essential stakeholders in the referral process with valuable perspectives. This review systematically explored their perceived facilitators and barriers to palliative care referral.Methods4 subject-specific databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, PsycINFO and EMBASE), 3 multidisciplinary databases (SCOPUS, Web of Science and Cochrane database) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In response to noted palliative care barriers, some academics and professionals in the field have also suggested that a rebranding effort may be necessary to move beyond these barriers. 42 , 43 Such recommendations focus on breaking the stigmas that tangle palliative care with end of life. In doing so, the hope is that palliative care could be rebranded to represent services that are integrated early in the chronic disease process leading to best care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In response to noted palliative care barriers, some academics and professionals in the field have also suggested that a rebranding effort may be necessary to move beyond these barriers. 42 , 43 Such recommendations focus on breaking the stigmas that tangle palliative care with end of life. In doing so, the hope is that palliative care could be rebranded to represent services that are integrated early in the chronic disease process leading to best care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a substantial number of persons, despite evidence of a high level of unmet needs, are referred at the near-end-of-life phase [25]. What is more, delayed referrals depend not only on late initiation of serious illness conversation or prognostication made by physicians, but may also be the result of patients' or family caregivers' wrong perspectives of palliative care [26]. This care could incorrectly be associated with an inferior form of treatment or even approaching death, while such referral can be emotionally devastating.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a substantial number of persons, despite evidence of a high level of unmet needs, the majority of patients are referred at the near the end of life phase [20]. What is more, delayed referrals depend not only on late initiation of serious illness conversation or prognostication made by physicians, but also may be the result of patients' or family caregivers' wrong perspectives of palliative care [21]. This care could incorrectly be associated as an inferior form of treatment or even approaching death, and such referral can be emotionally devastating.…”
Section: Discussionmentioning
confidence: 99%